2015
DOI: 10.1177/2056997115583583
|View full text |Cite
|
Sign up to set email alerts
|

Doubts about Religious Education in public schooling

Abstract: This article considers potential problems concerning Religious Education in public (state-funded) secondary schools in England in order to inform ongoing debates about religion in public education in the United States and elsewhere. Findings of empirical studies conducted in England are discussed in relation to arguments that critique Religious Education. It is argued that Religious Education as it is currently conceived and practised in England may be problematic for religious believers because it can misrepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…More recently, Kristjánsson (2013) asserted that character virtues do not rest on religious values. At the same time, religious education in Europe and North America has been increasingly separated from moral education and given a new remit to promote religious tolerance rather than the cultivation of religious commitment (Moulin, 2012(Moulin, , 2015. This is perhaps necessary for those negotiating ideological differences in order to promote aspirational goals and programs globally, including human rights and public health projects.…”
Section: Religion Education and Character Developmentmentioning
confidence: 99%
“…More recently, Kristjánsson (2013) asserted that character virtues do not rest on religious values. At the same time, religious education in Europe and North America has been increasingly separated from moral education and given a new remit to promote religious tolerance rather than the cultivation of religious commitment (Moulin, 2012(Moulin, , 2015. This is perhaps necessary for those negotiating ideological differences in order to promote aspirational goals and programs globally, including human rights and public health projects.…”
Section: Religion Education and Character Developmentmentioning
confidence: 99%
“…In addition, studies such as Garforth (1961) suggest that CRE as a subject faces difficulties identified by poor practice, including oversimplified, low-level classroom activities; poor resourcing, particularly the lack of suitably qualified expert teachers; and the poor articulation, conceptualization and understanding of its educational goals and aims (Conroy et al, 2013;Copley, 2005;Moulin, 2015).…”
Section: Factors Militating Against Effective Cre In Nigeriamentioning
confidence: 99%
“…But in this period, the chapel did not go without influence. For example, Margret Thatcher noted the impression the chapel addresses of Helen Darbishire made upon her, perhaps not insignificant because it was Thatcher's government that would go on to endorse multifaith religious education and acts of worship in all state-funded schools Moulin 2015;Thatcher 1995).…”
Section: The Story Of a Contested Buildingmentioning
confidence: 99%